ChemInform Abstract: Method of Continuous Variations: Applications of Job Plots to the Study of Molecular Associations in Organometallic Chemistry. Issue 3 (21st January 2014) - Renny, Joseph S.; Tomasevich, Laura L.; Tallmadge, Evan H.; Collum, David B.
Abstract Review: 107 refs.